TB Related Costs, Social Protection, Coping Strategies, and Social Consequences – A Survey among TB Patients Attending District Chest Clinics in Sri Lanka (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2024)
Introduction: Drivers of TB epidemic are closely linked with the social determinants of health. One of the End TB targets is to reach “Zero” catastrophic cost due to TB by 2035. The current study was planned to describe the TB related costs, the social protection, coping strategies and the social consequences experienced by TB patients.Methodology: A longitudinal study was conducted among 736 drug sensitive TB patients in nine districts from September 2021 to February 2022 using a multistage cluster sampling with probability proportional to size of the patients detected in the previous year. Data were collected using an interviewer administered questionnaire and the results were presented as proportions, median and inter quartile range (IQR).Results: Out of 750, 634 responded (84.5%). The median age (IQR) was 50 (23-27) years and one quarter (n=162, 25.6%) was in the age group of 55-64 years, majority (n=372, 58%) were males. Direct medical cost was the highest during pre-treatment period, whereas indirect costs increased over the TB episode contributing to 75% of per patient cost which was 127 USD. Around 16.8% of the patients experienced catastrophic cost due to TB. Around 30% of the participants who employed previously lost their jobs after diagnosis. Less than a quarter of patients had social protection by means of financial support and adopted coping strategies such as use of savings (46%) and loans from relatives (29%).Conclusion: Pre-treatment Direct medical costs and indirect costs after diagnosis are considerable while social protection is sub optimal for TB patients which need policy reforms.